EFFECTS OF CURCUMIN NANOPARTICLES AGAINST INDOMETHACIN INDUCED GASTRIC ULCER IN RAT - Abdulkareem, Gufran; Hasan, Bushra F.; Al-Masoudi, Wasfi A. (PT. Antis International Publisher, 2025)
Objective: Gastric ulcers (GUs) are a primary disorder affecting the upper gastrointestinal tract and are caused by gastric acid. The corrosive effects of pepsin and hydrochloric acid on the gastric mucosa can lead GUs. Compare the effect of curcumin and nanocurcumin with cimetidine on serum TC, TG, LDL, and HDL total protein and albumin levels in male rats with gastric ulcer. Method: Fifty male adult albino rats, with body weights ranging between 195–205 g where all the animals were categorized into five equal groups (each group containing 10 rats). Group 1: normal group, Group 2: indomethacin group, Group 3: indomethacin with curcumin, Group 4: indomethacin with nanocurcumin, Group 5: indomethacin with cimetidine. Blood samples (4 ml) were then placed into tubes without any anticoagulant, after centrifuging serum samples were then used for determining TC, TG, LDL, HDL, total protein and albumin levels in the animals. Results: Se/NP had a spherical, smooth nanoparticles, nanometre-sized. Oral administration of nanocurcumin caused marked improvement in HDL concentration and LDL concentration compared with gastric ulcer group and there were non-significant changes compared with normal group. Oral administration of nanocurcumin and cimetidine revealed a significant increase at (p≤0.05) level in serum albumin concentration when compared with gastric ulcer group and reach to normal group. Novelty: In rats with gastric ulcers caused by Indomethacin, the prepared nanocurcumin proved to be much more effective than curcumin. These results serve as a foundation for additional pharmacological investigation that could result in the creation of novel drug formulations.